If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+8=3(2x+4+2)
We move all terms to the left:
x+8-(3(2x+4+2))=0
We add all the numbers together, and all the variables
x-(3(2x+6))+8=0
We calculate terms in parentheses: -(3(2x+6)), so:We get rid of parentheses
3(2x+6)
We multiply parentheses
6x+18
Back to the equation:
-(6x+18)
x-6x-18+8=0
We add all the numbers together, and all the variables
-5x-10=0
We move all terms containing x to the left, all other terms to the right
-5x=10
x=10/-5
x=-2
| 3/10x-4x+4/5=3/5 | | 3(7x-2)=99 | | -x+7=-(2x+3)+15 | | 3(2x+5)=13+2x+2+4x | | 8=2+3s | | 1/15=4a-3 | | 6x-33=5x-6 | | 17/21-4/6=a | | -42=7/5y | | 7x-17=5x-7 | | 2x-5=11+6x | | 49=7^2x-1 | | 9x-19=10x+10 | | 8n-(5n+4)=14 | | -1.28=((x-25)/5) | | 15x+8=7x+16 | | 1.222+3x=13 | | 3(3x-2)=39 | | 5=4/7(21+3x)=41 | | 4x-30=126 | | {4}{5}45k+7={3}{4}34k+3 | | 50*45*x=56250 | | 3(3x-2)=39 | | 21+4d=-7(6d-3)d=0 | | 6k+k=-2k | | A=2(1.2+z+1.2z) | | 2x=(1/4)x+7 | | 4x-5=2x-19 | | -8x+12=4x+4 | | 5(w+3)+3w=w-34 | | 6z=4; | | -60=v/6 |